Enhancing English Language Learning in Libyan Primary Schools through Gamification: Guidelines Development (Faculty of Education Scientific Journal, 2024)
: The English language is widely recognized as a global language, playing a pivotal role in various domains such as education, and business. However, there is a lack of guidelines specifically tailored to measure the effect of gamification on English language learning among Libyan primary school students. This study aims to develop guidelines using a building and evaluating method. To establish these guidelines, the most commonly used and important factors were collected, and expert validation was performed to ensure the validity of these factors. The results confirmed that factors such as motivation, engagement, performance, and participation are valid and can be effectively employed for measuring the impact of gamification on English language learning among Libyan primary school students. The developed guidelines, based on identified factors and expert validation, serve as a valuable resource for educators and researchers seeking to leverage gamification in the pursuit of improved English language proficiency among Libyan primary school students.
Keywords: Gamification; Guideline; English Language Learning; Primary School